2011
DOI: 10.1097/med.0b013e3283424b37
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic effects of obesity causing disease in childhood

Abstract: Physicians should not only warn obese children and their families about the long-term consequences of obesity for which they are at risk in adulthood, they should also screen for the many diseases that may already be present.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
54
0
4

Year Published

2011
2011
2018
2018

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 73 publications
(58 citation statements)
references
References 43 publications
0
54
0
4
Order By: Relevance
“…Childhood overweight is associated with serious consequences for health and well-being both during childhood years and in adulthood (3)(4)(5)(6)(7). Effective early preventive strategies are therefore urgently needed.…”
Section: Introductionmentioning
confidence: 99%
“…Childhood overweight is associated with serious consequences for health and well-being both during childhood years and in adulthood (3)(4)(5)(6)(7). Effective early preventive strategies are therefore urgently needed.…”
Section: Introductionmentioning
confidence: 99%
“…Also, in pediatric autopsies of overweight and obese children between the ages of 2-19 years, Schwimmer et al (Abrams & Levitt Katz, 2011) found non-alcoholic fatty livers in the majority of cases. Twenty-three percent of those cases had progressed to steatohepatitis, which can develop into fibrosis and cirrhosis of the liver.…”
Section: Gastrointestinalmentioning
confidence: 99%
“…Increased Gastrointestinal (GI) disturbances such as constipation, gastroesophageal reflux (Philippi-Hohne, 2010), Irritable Bowel Syndrome, and abdominal pain (Abrams & Levitt Katz, 2011) have been found in obese children. Also, in pediatric autopsies of overweight and obese children between the ages of 2-19 years, Schwimmer et al (Abrams & Levitt Katz, 2011) found non-alcoholic fatty livers in the majority of cases.…”
Section: Gastrointestinalmentioning
confidence: 99%
See 2 more Smart Citations